The impact of social networking sites on youths' behavior / Nur Alia Khalidah Mohd Rafta ... [et al.] - Mohd Rafta, Nur Alia Khalidah; Ibrahim, Ainin Nur Sofiya; Ismail, Nur Ain Alisha; Hilal, Nur Afini; Muhamad @ Mohamad Tohel, Nuradlyn Syazana; Mohd Zaki, Aris Syahmi (2018)
This research paper is focusing on the Impact of Social Networking Sites (SNS) on Youths' Behavior. We have decided to choose this topic as our research because it has been one of the most common and typical issues related in Malaysia especially in Klang Valley populations. These impacts of social networking sites on youths' behaviour have always been overwhelming and with so many people now on social media tweeting links and posting selfies and sharing YouTube videos, it sure can get pretty huge and noisy. Therefore, we would like to study the advantages of social networking sites focusing on Twitter and Instagram. This research is conducted because the researchers would like to learn more regarding the benefits of social media towards the younger generations. Also, we also would like to study the impact of youths' behaviour. Through this, we learned a deeper understanding of youths' behaviour when it comes to using social media platform. Furthermore, we seek to identify the reasons why people would prefer using on line media rather than traditional media. From the findings that we have concluded, we analysed that social networking sites (SNS) is capable of creating a healthy environment and technological advances, as an academic tool for a wider audience and practices of social media creates an invasion of privacy. Through this study, the researchers used a qualitative research by using the in-depth interview towards the respondents based on our purposive sampling for methodology.